DEVELOPMENT OF SMALL HAND MATORICS IN CHILDREN IN PRESCHOOL EDUCATION - Matluba Egamberdiyeva; Dilnoz Mutalova (Bright Mind Publishing, 2025)
This article explores the methods and innovative games used to develop fine motor skills. Particularly, the development of fine motor skills directly influences the formation of intellectual, creative, and linguistic abilities. Pedagogical approaches, the Montessori method, didactic games, and modern technologies are analyzed in terms of their effectiveness in enhancing fine motor development. Additionally, the article examines legal and regulatory documents in the educational system of Uzbekistan and their application in practice.
Keywords: Fine motor skills, cognitive development, preschool education, Montessori method, didactic games, innovative technologies, physical development, intellectual skills, pedagogical methods, child psychology, age characteristics, educational standards.